As facetas de conhecimento na organização e gestão do currículo em escolas públicas de tempo integral - Andrade, Andrea Cianflone Zacharias de (2018)
This study investigated the organization and management of the curriculum in the context of “fulltime” public elementary and middle school. The research theme is justified by the challenge of understanding different contexts and possibilities for “fulltime” schools. The research considered the guiding principles that are established in the official national and municipal documents, as well as the experiences of “fulltime” schools in Brazil, in a city in the state of São Paulo. This study questions how the curriculum in “fulltime” schools is being organized and managed, and presents two main questions: How is the curriculum of “fulltime” schools being organized and managed? What facets of knowledge are presented in the options available in the additional periods of “fulltime” schools”? The objective of this research focusses on identifying and analyzing the organization and management of the curriculum in the additional periods of “fulltime” schools, in order to map out and identify which facets of knowledge are offered in the activities that complement the curriculum in the regular school period. The theoretical foundations were based on the concepts of ideology and curriculum as defended by Michael Apple , curriculum as a social construction proposed by Ivor Goodson and powerful knowledge created by Michael Young. The methodology was founded on the illuminative evaluation approach described by Malcolm Parlett & David Hamilton. For this purpose, data was collected with teachers and pedagogical coordinators in two schools that have been offering “fulltime” projects in the city of São José dos Campos, as well as with the coordinator of the program of "fulltime" schools in the referred city, in order to identify how curriculum organization and management have been developed. The research results partiatlly comprove the hypotheses that were raised under three perspectives: the activities offered in the additional periods of the school are characterized by bringing a body of knowledge which is not delivered in the regular school hours; therefore, not clearly related to powerful knowledge; the school reproduces the same ideology both in its core curriculum and in the complementary activities which happen after school hours, and the activities offered in the “fulltime” program, after the school hours, are selected according to the social and cultural context of the school and its surroundings